SPACE :IDENTIFICATIONS AND DEFINITIONS Case study on The Traditional Malay Dwellings of West Kalimantan Indonesia - Zairin Zain (Universitas Muhammadiyah Jakarta, 2011)
ABSTRACT. A house has function as a shelter for the occupants from directly physical influence of the environmental changes such as climate or weather. Each object of traditional Malay dwellings which taken as case study represent the type of traditional Malay dwellings in each city across West Kalimantan. According to the indentifications on the space, researcher have found the definitions of respective rooms within The Traditional Malay Dwellings of West Kalimantan which is related to the religious belief of the Malays. The teaching of Islam is manifested in the design of house’s form and elements that support the space inside the dwellings. Keywords : traditional dwelling, space, identification, definitions ABSTRAK. Sebuah rumah memiliki fungsi sebagai pelindung bagi penghuninya dari pengaruh fisik secara langsung dari perubahan lingkungan seperti iklim atau cuaca. Setiap obyek dari hunian tradisional Melayu yang diambil sebagai studi kasus mewakili setiap tipe hunian tradisional Melayu pada setiap kota di Kalimantan Barat. Berdasarkan identifikasi ruang, peneliti menemukan definisi dari ruang tertentu dalam hunian tradisional Melayu di Kalimantan Barat yang dikaitkan dengan kepercayaan agama dari orang Melayu. Ajaran Islam diwujudkan dalam disain bentuk rumah dan elemen-elemen yang mendukung ruang di dalam hunian-hunian tersebut. Kaca kunci: hunian tradisional, ruang, identifikasi, definisi